Modelization of Dioctyl Phthalate Transfer from Plasticized PVC Disks Dipped into Sunflower Oil - FERTIKH, NADIA; MESSADI, DJELLOUL (Asian Journal of Chemistry, 2010)
Plasticized PVC packaging of liquid foodstuffs leads to a simultaneous diffusion: additives (plasticizer in particular) - liquid. The temperature used currently higher than the PVC glass transition temperature Tg. In such circumstances the diffusion is generally Fickian, with a diffusion depending on the concentration of the liquid and plasticizer. Nevertheless, when the liquid is an edible oil this dependence may be adjusted by neglecting the small amounts of oil which diffuse into the polymer. A simplified predictive mathematical model of dioctyl phthalate (DOP) plasticizer migration from PVC into sunflower oil was tested. The statistical results show that the computed DOP concentrations into the edible oil, as well as computed profiles of DOP concentration developed through PVC matrix correlate with measured ones, with a P-value = 0.001. Diffusivities at various thicknesses inside the PVC disk vary exponentially in term of reciprocal plasticizer local concentration.